Preparation process of high-strength and breathable cup cover paper

CN122280023BActive Publication Date: 2026-10-09临朐玉龙造纸有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610738190.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-10-09
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种高强度透气杯盖纸的制备工艺,解决目前杯盖纸材料中力学强度与透气性能难以兼顾,以及核壳微粒在纸浆体系中分散稳定性与残留控制难以兼顾的痛点问题

Benefits of technology

1.通过在纸浆纤维浆料中引入多孔淀粉@柠檬酸交联阳离子淀粉核壳微粒,多孔淀粉核提供微孔支撑,柠檬酸交联阳离子淀粉壳层增强微粒与纤维的吸附结合,使纸页在不设置连续塑料淋膜层的条件下兼顾抗张强度和透气性能,改善单纯致密化增强导致透气性下降的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122280023B_ABST
    Figure CN122280023B_ABST
Patent Text Reader

Abstract

The application belongs to the field of food packaging paper base materials, and provides a preparation process of high-strength breathable cup cover paper. In the paper pulp fiber slurry, porous starch citric acid cross-linked cationic starch core-shell microparticles are introduced, and the paper page system without a continuous plastic coating layer is constructed through shaping, pressing, drying and hot pressing finishing, so that the porous starch core is beneficial to maintaining the pore structure and the breathable performance of the paper page, the cross-linked cationic starch shell layer enhances the fiber combination and the microparticle retention, the cup cover paper with the higher tensile index, the suitable breathability, the stable microparticle distribution and the lower free citric acid residual level is obtained, the problems that the enhanced densification weakens the breathability, the porous component reduces the strength, and the dispersion stability and the residual control are difficult to consider are solved, and the cup cover paper can be used as a paper base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of paper-based materials for food packaging, and specifically to a preparation process for a high-strength, breathable cup lid paper. Background Technology

[0002] With the rapid development of takeaway beverage, freshly made coffee, tea, and fast food packaging, paper cup lids are gradually taking on the important function of replacing traditional plastic cup lids. Cup lid paper not only needs to maintain sufficient stiffness, tensile strength, and dimensional stability during pressing, die-cutting, thermoforming, and snap-fitting, but also needs to maintain structural integrity under conditions of hot beverage steam, cold beverage condensation, and short-term contact with moisture. On the other hand, cup lid paper needs to retain appropriate ventilation channels when covering beverages to alleviate moisture accumulation, paper softening, and localized bulging, while meeting the requirements of food contact packaging for low migration, low odor, and recyclability. Therefore, developing cup lid paper that combines high mechanical strength, suitable ventilation, a stable fiber network, and a non-continuous plastic coating layer is of great significance for improving the reliability of paper-based food packaging, reducing reliance on plastics, and expanding the application scenarios of paper-based packaging.

[0003] Existing paper cup lid technologies primarily improve the fastening strength and durability of paper cup lids from the perspectives of structural forming, surface coating, or densification treatment. For example, Chinese patent CN204979661U discloses an environmentally friendly paper cup lid, mentioning in its background that paper cup lids are prone to softening under the influence of hot beverage steam, affecting their usability; Chinese patent CN106335702B discloses a paper cup lid and its processing technology, focusing on improving the lid structure through pressing, bottom folding, and knurling. While these technologies help improve the forming and fastening stability of the lid, they still fall short in addressing the issues of internal fiber bonding, maintaining air permeability channels, and balancing strength and air permeability under conditions without continuous plastic coating. Generally, increasing strength leads to denser paper sheets and compressed pores, while retaining pores or introducing porous components may weaken the inter-fiber bonding; simultaneously, particulate additives with insufficient dispersion stability are prone to localized agglomeration, and increasing hydrophilicity and charge may increase migratable components, making it difficult to simultaneously achieve low migration and dispersion stability. Summary of the Invention

[0004] The purpose of this invention is to provide a preparation process for high-strength breathable cup lid paper, which solves the problems of difficulty in balancing mechanical strength and breathability in current cup lid paper materials, as well as difficulty in balancing the dispersion stability and residue control of core-shell microparticles in the pulp system.

[0005] Porous components, while beneficial for retaining gas channels, may weaken inter-fiber bonding. Increased densification, while improving tensile strength, may compress pores and reduce air permeability. This invention utilizes porous starch cores to maintain the paper's pore structure and air permeability, and a citric acid-crosslinked cationic starch shell to enhance fiber adsorption and microparticle fixation. Furthermore, the timing of addition, pressing and drying, and hot-press finishing are used to jointly regulate the paper network, achieving a synergistic balance between strength and air permeability.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A process for preparing a high-strength, breathable cup lid paper, characterized by comprising the following steps: S1. Provides pulp fiber pulp and porous starch@citric acid crosslinked cationic starch core-shell microparticles; S2. The porous starch@citric acid crosslinked cationic starch core-shell microparticles are added to the pulp fiber pulp to form a pulp system containing porous starch@citric acid crosslinked cationic starch core-shell microparticles; S3. The pulp system containing porous starch@citric acid crosslinked cationic starch core-shell microparticles is formed, pressed, dried and hot-pressed to obtain high-strength breathable cup lid paper; The high-strength breathable cup lid paper does not have a continuous plastic coating layer. Based on 100 parts by weight of the total amount of the oven-dry final components in the high-strength breathable cup lid paper, the high-strength breathable cup lid paper comprises: 90.0–98.0 parts by weight of pulp fiber, wherein the pulp fiber comprises one or more of softwood pulp, hardwood pulp, bamboo pulp and bagasse pulp; Porous starch@citric acid crosslinked cationic starch core-shell microparticles 2.0–10.0 parts by weight; The sum of the weight parts of the pulp fiber and the porous starch@citric acid crosslinked cationic starch core-shell microparticles is 100 parts by weight.

[0007] Furthermore, the porous starch@citric acid crosslinked cationic starch core-shell microparticles include a porous starch core and a citric acid crosslinked cationic starch shell layer that at least partially coats the surface of the porous starch core; The porous starch@citric acid crosslinked cationic starch core-shell microparticles have a D50 of 8–25 μm, a shell thickness of 0.10–0.80 μm, and a coating rate of 75–98%.

[0008] Furthermore, the porous starch core is obtained by enzymatic treatment of starch; the cationic starch is obtained by etherification of starch with a cationic etherifying agent under alkaline conditions; and the citric acid crosslinked cationic starch shell is formed by crosslinking the cationic starch with a citric acid crosslinking agent.

[0009] Furthermore, the porous starch@citric acid crosslinked cationic starch core-shell microparticles are prepared through the following steps: A1. Provides porous starch cores and cationic starch; A2. Disperse the porous starch core in an aqueous medium, add the cationic starch, and adjust the solid content of the system; A3. Add citric acid crosslinking agent and adjust pH, and under heating and stirring conditions, allow the cationic starch to adsorb onto the surface of the porous starch core to obtain a dispersion; A4. The dispersion is dried to obtain pre-coated particles; A5. The pre-coated particles are heat-cured at 115–145°C for 5–30 min to allow the citric acid crosslinking agent to form an ester crosslink with the cationic starch, thereby obtaining a heat-cured product; A6. The thermosetting product is washed and dried to obtain the porous starch@citric acid crosslinked cationic starch core-shell microparticles.

[0010] Further, in step A6, the thermosetting product is washed and dried to obtain the porous starch@citric acid crosslinked cationic starch core-shell microparticles; the free citric acid content of the porous starch@citric acid crosslinked cationic starch core-shell microparticles is 0.02–0.80 wt%, based on the mass of the porous starch@citric acid crosslinked cationic starch core-shell microparticles.

[0011] Furthermore, the porous starch core is prepared through the following steps: B1. Disperse starch in an aqueous medium, add a buffer system, and adjust the pH to 4.6–6.2; B2. Add medium-temperature α-amylase and amylase to the dispersion obtained in step B1, and hydrolyze for 1–4 h under heating conditions of 38–58 °C. B3. When the starch hydrolysis weight loss reaches 10–35 wt%, heat the system to 85–100℃ and hold for 10–30 min to inactivate the enzyme; B4. Wash the solid obtained in step B3 until the pH of the washing solution is 5.5–7.5, and dry it at 45–70°C for 4–16 h to obtain the porous starch core; The porous starch core has a D50 of 6.4–23.4 μm, a pore size of 0.30–5.00 μm, and a moisture content of 6–13 wt%.

[0012] Furthermore, the cationic starch is prepared by the following steps: C1. Mix starch, aqueous medium and inorganic salt to obtain starch slurry; C2. Add an alkaline regulator to the starch slurry to adjust the pH to 10.5–12.0; C3. Add a cationic etherifying agent to the system obtained in step C2 and etherify it under heating conditions of 35–55°C for 2–6 hours; C4. Adjust the pH to 6.0–7.5, then wash 2–5 times and dry at 40–65°C for 6–18 h to obtain the cationic starch; The cationic starch has a degree of cationic substitution of 0.015–0.080, a residual cationic etherifying agent content of no more than 200 mg / kg based on the mass of the cationic starch, and a moisture content of 6–13 wt%.

[0013] Furthermore, in the porous starch@citric acid crosslinked cationic starch core-shell microparticles, the dry weight ratio of the porous starch core to the citric acid crosslinked cationic starch shell is 100:8–35, the degree of cationic substitution of the citric acid crosslinked cationic starch shell is 0.010–0.070, and the retention rate of the porous starch@citric acid crosslinked cationic starch core-shell microparticles in the high-strength breathable cup lid paper is 70–98%.

[0014] Furthermore, the pulp fiber includes softwood pulp, as well as one or more of hardwood pulp, bamboo pulp, or bagasse pulp; the basis weight of the high-strength breathable cup lid paper is 240–360 g / m³. 2 The air permeability is 0.15–1.20 μm / (Pa·s), and the tensile index is 45–85 N·m / g.

[0015] Furthermore, in step S2, the mass concentration of the pulp fiber slurry is 0.3–1.2 wt%, the pH is 5.5–7.5, and the porous starch@citric acid crosslinked cationic starch core-shell microparticles are added 5–30 min before entering the forming wire.

[0016] Further, in step S3, the formed wet paper sheet is subjected to pressing and drying treatment. The pressing linear pressure is 80–250 kN / m, the drying temperature is 80–120°C, and the wet paper sheet is dried to a moisture content of 4–10 wt%.

[0017] Furthermore, in step S3, the hot pressing finishing temperature is 90–135℃, the linear voltage is 30–180kN / m, and the time is 0.2–5.0s.

[0018] Furthermore, the breakage rate of the porous starch@citric acid crosslinked cationic starch core-shell microparticles after entering the pulp fiber slurry is calculated based on the particle size change. The D50 of the core-shell microparticles before addition is denoted as D500, and the D50 of the core-shell microparticles obtained by sampling before entering the pulp fiber slurry and before entering the forming wire is denoted as D501. The breakage rate is calculated as (D500-D501) / D500×100%, and the resulting breakage rate is 1–15%.

[0019] Furthermore, in the preparation of the porous starch core, 100 parts by weight of starch are dispersed in 250–600 parts by weight of deionized water, a buffer system formed by anhydrous citric acid and sodium citrate dihydrate is added, the pH of the system is adjusted to 4.6–6.2, and then 0.05–0.60 parts by weight of mesophilic α-amylase and 0.02–0.30 parts by weight of amylase are added. The mixture is hydrolyzed at 38–58°C for 1–4 hours under air atmosphere and normal pressure to obtain a dispersion system containing hydrolyzed starch particles.

[0020] Furthermore, the mass and specific activity of the enzyme preparations of the mesophilic α-amylase and the amyloglucosidase are recorded before addition, and the total enzyme activity entering the hydrolysis system is calculated by multiplying the enzyme preparation mass and specific activity; the total enzyme activity is recorded in correspondence with the oven-dry mass of starch, which is used to control the hydrolysis weight loss of the same batch of hydrolysis system to reach 10–35 wt%.

[0021] Furthermore, the hydrolysis weight loss is calculated as "hydrolysis weight loss = difference between the oven-dry weight of starch before reaction and the oven-dry weight of the solid after hydrolysis, washing, and drying / oven-dry weight of starch before reaction × 100%"; when the hydrolysis weight loss reaches 10–35 wt%, the system is heated to 85–100℃ and held for 10–30 min to inactivate the enzyme, and then the obtained solid is washed with deionized water until the pH of the washing solution is 5.5–7.5, and then dried at 45–70℃ for 4–16 h to obtain porous starch cores.

[0022] Furthermore, the porous starch cores are subjected to particle size, pore size and moisture content detection before entering the coating step; the particle size is recorded as D50, the pore size is recorded as the arithmetic mean of the opening size of multiple pores in the microscopic image, and the moisture content is calculated as the mass change before and after drying. The obtained porous starch cores are used as the solid input for the cationic starch adsorption step.

[0023] Furthermore, in the preparation of the cationic starch, 100 parts by weight of starch, 120–300 parts by weight of deionized water and 5–20 parts by weight of sodium chloride are mixed to form a starch slurry. 2–8 parts by weight of sodium hydroxide are added and the pH of the system is adjusted to 10.5–12.0. Then, 10–35 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride are added, and the mixture is etherified at 35–55°C for 2–6 hours under air atmosphere and normal pressure to obtain a cationization reaction system.

[0024] Furthermore, after the etherification reaction, the pH of the cationization reaction system is adjusted to 6.0–7.5 with hydrochloric acid, then washed 2–5 times with deionized water, and dried at 40–65°C for 6–18 h to obtain cationic starch; the cationic starch is used as a shell material to enter the adsorption step on the surface of porous starch core.

[0025] Furthermore, the degree of cation substitution of the cationic starch is calculated by nitrogen content. The test object is a cationic starch sample after washing and drying. The nitrogen content N% of the sample is recorded (where N is the mass percentage of nitrogen content), and the degree of cation substitution is calculated by DS=162×N / (14×100-151.6×N). The degree of cation substitution is used to characterize the degree of cationization of cationic starch before it enters the shell preparation step.

[0026] Furthermore, in the preparation of the porous starch@citric acid crosslinked cationic starch core-shell microparticles, 100 parts by weight of porous starch cores are dispersed in deionized water, 8-35 parts by weight of cationic starch (dry basis) are added to adjust the solid content of the system to 10-35 wt%, and then 1-8 parts by weight of anhydrous citric acid are added and the pH is adjusted to 3.5-5.5. The mixture is stirred at 45-70°C for 20-90 min under air atmosphere and normal pressure to allow the cationic starch to adsorb onto the surface of the porous starch cores, thereby obtaining a dispersion containing pre-coated particles.

[0027] Furthermore, the operating temperature of the cationic starch adsorption step is lower than the gelatinization initiation temperature of the porous starch core used; the gelatinization initiation temperature of the porous starch core is determined by differential scanning calorimetry, and the endothermic peak initiation temperature in the differential scanning calorimetry curve is taken as the gelatinization initiation temperature to limit the upper temperature limit of the cationic starch adsorption step.

[0028] Furthermore, the dispersion is spray-dried or hot-air dried to obtain pre-coated particles; when spray-dried, the inlet air temperature is 120–170℃ and the outlet air temperature is 60–90℃; when hot-air dried, the temperature is 50–80℃ and the time is 4–12h; the obtained pre-coated particles enter the thermosetting step.

[0029] Furthermore, the pre-coated particles are thermocured at 115–145°C for 5–30 min to form a citric acid crosslinked cationic starch shell with anhydrous citric acid, thus obtaining a thermocure product; the thermocure product is rinsed with deionized water 1–3 times and dried at 45–70°C for 2–8 h to obtain porous starch@citric acid crosslinked cationic starch core-shell microparticles.

[0030] Furthermore, the D50 of the porous starch@citric acid crosslinked cationic starch core-shell microparticles was determined by laser diffraction particle size distribution. The sample to be tested was a particle dispersion of the core-shell microparticles after washing and drying and then dispersing them in an aqueous medium. The D10, D50 and D90 of the volume distribution were recorded. The particle size distribution of the pre-coated particles and the core-shell microparticles after heat curing in the same batch were measured to record the particle size changes before and after heat curing.

[0031] Furthermore, the shell thickness was determined using a transmission electron microscope cross-sectional image. The sample to be tested was porous starch@citric acid cross-linked cationic starch core-shell microparticles after washing and drying. After embedding and slicing, particle cross-sectional images were obtained. The radial distance from the outer contour of the porous starch core to the outer contour of the shell was recorded on multiple particle cross-sections, and the arithmetic mean of the recorded radial distances was used as the shell thickness.

[0032] Furthermore, the coating rate is expressed as the proportion of the shell-covered perimeter in the cross-sectional image of a transmission electron microscope. The total perimeter of the outer contour of the porous starch core and the perimeter of the outer contour covered by the citric acid cross-linked cationic starch shell are recorded in multiple particle cross-sectional images, and the coating rate is calculated as "coating rate = perimeter of the outer contour covered by the shell / total perimeter of the outer contour of the porous starch core × 100%".

[0033] Furthermore, the free citric acid content is determined using washed and dried porous starch@citric acid cross-linked cationic starch core-shell microparticles as the test sample. The test sample is extracted with deionized water to obtain an aqueous extract. The peak area of ​​citric acid is recorded using high performance liquid chromatography with external standard method, and the mass of free citric acid is calculated according to the external standard curve. The percentage of the mass of free citric acid to the mass of the test sample is taken as the free citric acid content.

[0034] Furthermore, the dry weight ratio of the porous starch core to the citric acid cross-linked cationic starch shell in the porous starch@citric acid cross-linked cationic starch core-shell microparticles is calculated based on the dry weight of the core-shell microparticles after washing, the dry weight of the porous starch cores fed in, and the weight of the soluble starch component in the washing liquid; the material balance result is used to record the composition of the core-shell microparticles before entering the pulp fiber pulp.

[0035] Furthermore, the surface potential of the porous starch@citric acid crosslinked cationic starch core-shell microparticles was tested using an aqueous dispersion system. Before the test, the core-shell microparticles were dispersed in an aqueous medium with a pH of 5.5–7.5, and the zeta potential value was recorded. The obtained surface potential ranged from +5mV to +35mV.

[0036] Furthermore, the pulp fiber comprises 35–75 wt% softwood pulp and a total of 25–65 wt% hardwood pulp, bamboo pulp, or bagasse pulp, wherein the wt% is based on the oven-dry weight of the pulp fiber; after the pulp fiber is dispersed to form a pulp fiber slurry with a mass concentration of 0.3–1.2 wt% and a pH of 5.5–7.5, it enters the core-shell microparticle addition step.

[0037] Furthermore, the porous starch@citric acid crosslinked cationic starch core-shell microparticles are added to the pulp fiber slurry 5–30 minutes before entering the forming wire. The pulp system after addition is formed, pressed and dried. The pressing linear pressure is 80–250 kN / m, the drying temperature is 80–120°C, and the wet paper is dried to a moisture content of 4–10 wt%.

[0038] Furthermore, the dried paper sheet undergoes hot pressing finishing at a temperature of 90–135℃, a linear pressure of 30–180 kN / m, and a time of 0.2–5.0 s, resulting in a thickness of 0.35–0.75 mm and a density of 0.45–0.90 g / cm³. 3 High-strength breathable cup lid paper.

[0039] Furthermore, the breakage rate of the porous starch@citric acid crosslinked cationic starch core-shell microparticles after entering the pulp fiber slurry is calculated based on the particle size change. The D50 of the core-shell microparticles before addition is denoted as D500, and the D50 of the core-shell microparticles obtained by sampling before entering the pulp fiber slurry and before entering the forming wire is denoted as D501. The breakage rate is calculated as (D500-D501) / D500×100%, and the resulting breakage rate is 1–15%.

[0040] Furthermore, the retention rate of the porous starch@citric acid crosslinked cationic starch core-shell microparticles in high-strength breathable cup lid paper is calculated using the content of cationic substituent nitrogen as a tracer parameter. The nitrogen content of pulp fiber before the addition of core-shell microparticles, the nitrogen content of paper after the addition of core-shell microparticles, and the nitrogen content of core-shell microparticles are measured respectively. After deducting the background of pulp fiber nitrogen content, the dry basis mass of core-shell microparticles in the paper is converted and calculated according to "Retention rate = Dry basis mass of core-shell microparticles in paper / Dry basis mass of core-shell microparticles added to pulp fiber pulp × 100%".

[0041] Furthermore, the coefficient of variation of the distribution of the porous starch@citric acid crosslinked cationic starch core-shell microparticles in the thickness direction of the high-strength breathable cup lid paper is calculated by the cross-sectional image of the paper sheet. The thickness direction of the paper sheet is divided into upper, middle and lower layers, and the number or area ratio of core-shell microparticles in each layer is counted. The coefficient of variation is calculated according to "coefficient of variation = standard deviation of distribution data of three layers / average value of distribution data of three layers × 100%", and the obtained coefficient of variation is 5–25%.

[0042] Furthermore, the core-shell particles located in the fiber cross-section of the paper sheet are identified by cross-sectional microscopic images. The fiber cross-section is the area in the same cross-sectional image where two pulp fibers are in contact or overlap with each other. The core-shell particles located in this area and simultaneously in contact with the surfaces of the two pulp fibers are recorded as fiber cross-section particles. The statistical results of the fiber cross-section particles are used to characterize the distribution state of the core-shell particles in the pulp fiber network.

[0043] Furthermore, the air permeability of the high-strength breathable cup lid paper is determined according to GB / T 458-2008. The test sample is a paper sheet sample after equilibrium under standard atmospheric conditions specified in GB / T 10739-2023. The air permeability value is recorded and expressed in μm / (Pa·s). The tensile index is determined according to GB / T 12914-2018. The tensile strength and basis weight of the sample are recorded, and the tensile index is calculated according to the ratio of tensile strength to basis weight.

[0044] As a concept of this invention, the present invention employs a papermaking design that combines pulp fiber pulp with porous starch@citric acid cross-linked cationic starch core-shell microparticles, primarily to achieve a synergistic balance between tensile strength and air permeability. Existing cup lid paper, if its mechanical strength is improved by enhancing compaction or increasing fiber bonding, tends to have compressed pores, reducing moisture passage space and consequently decreasing air permeability. Conversely, if pores are retained or porous particles are introduced to maintain air permeability, effective contact between fibers may be reduced, affecting paper strength and forming stability. This invention provides internal channels through porous starch cores, enhances the bonding and retention of microparticles and fibers through a citric acid cross-linked cationic starch shell, and adjusts the paper network through forming, pressing, drying, and hot-pressing finishing. This ensures that the porous structure does not simply weaken strength, and the strengthening treatment does not simply close gas channels, thereby achieving a strength-air permeability balance suitable for cup lid paper.

[0045] Porous starch cores primarily serve to maintain microporous channels for gas passage in paper sheets. However, their presence alone or excessive proportion can weaken direct fiber contact and may lead to localized aggregation within the pulp system, reducing the tensile strength of the paper. Citric acid-crosslinked cationic starch shells mainly enhance adsorption, fixation, and low migration between core-shell particles and pulp fibers. However, excessively thick crosslinked shells or high cationization levels can increase system densification and localized adhesion, restricting air permeability. This invention achieves a balance between the air permeability contribution of the porous structure and the fiber bonding contribution of the shell by matching the dry weight ratio of porous starch cores to citric acid-crosslinked cationic starch shells, shell thickness, coating rate, addition timing, and hot-pressing finishing conditions. This balances the inherently contradictory properties of strength and air permeability.

[0046] Beneficial technical effects 1. By introducing porous starch@citric acid cross-linked cationic starch core-shell microparticles into the pulp fiber pulp, the porous starch core provides microporous support, and the citric acid cross-linked cationic starch shell enhances the adsorption and binding of microparticles with fibers, so that the paper sheet can take into account both tensile strength and air permeability without setting a continuous plastic coating layer, thus improving the problem of reduced air permeability caused by simple densification reinforcement.

[0047] 2. By controlling the D50, shell thickness, coverage, and dry weight ratio of the core-shell microparticles, the microparticles can maintain a suitable size and interfacial bonding state in the fiber network, reducing the strength loss caused by the direct addition of porous particles, while avoiding excessive shell thickness leading to excessive paper density, which is conducive to forming a coordinated relationship between strength, air permeability, and forming stability.

[0048] 3. By forming porous starch cores through enzymatic treatment and constructing a shell through cationic starch and citric acid crosslinking agent, the dispersion and retention of microparticles in aqueous pulp systems can be improved, and the migration risk caused by free citric acid and residual cationic etherifying agent can be reduced, thereby improving the problem that existing particulate additives are difficult to balance between dispersion stability and low migration.

[0049] 4. By limiting the timing of core-shell microparticle addition, pulp fiber concentration, press line pressure, drying temperature, and hot pressing finishing conditions, the microparticle distribution and paper density in the fiber cross-section area can be adjusted during the forming process, reducing the impact of local agglomeration or over-compaction on performance, making cup lid paper suitable for hot beverage, cold beverage, and takeaway catering packaging scenarios. Attached Figure Description

[0050] Figure 1 The TEM shell thickness probability density distribution diagrams are for Example 1, Comparative Example 10, and Comparative Example 11.

[0051] Figure 2 Box plots of TEM shell thickness for Example 1, Comparative Example 10, and Comparative Example 11.

[0052] Figure 3 The cumulative distribution of TEM coverage rate for Example 1, Comparative Example 10, and Comparative Example 11 is shown in the figure.

[0053] Figure 4 Box plots of TEM coverage for Example 1, Comparative Example 10, and Comparative Example 11.

[0054] Figure 5 The above are the superimposed FTIR absorbance spectra of Example 1, Comparative Example 5, and Comparative Example 11.

[0055] Figure 6 The HPLC chromatograms of free citric acid for Examples 1, 5, and 11 are shown.

[0056] Figure 7 The image shows the scatter plot of the free citric acid content for Example 1, Comparative Example 5, and Comparative Example 11.

[0057] Figure 8 The scatter plot shows the mean of the core-shell particle retention rates for Example 1, Comparative Example 6, and Comparative Example 10.

[0058] Figure 9The scatter plot shows the mean of nitrogen content after background subtraction for Example 1, Comparative Example 6, and Comparative Example 10.

[0059] Figure 10 The paper thickness distribution diagrams for Example 1, Comparative Example 6, and Comparative Example 11 are shown in the three-layer distribution diagrams.

[0060] Figure 11 The scatter plot shows the mean of the coefficient of variation in the thickness direction of Example 1, Comparative Example 6, and Comparative Example 11.

[0061] Figure 12 The above is a scatter plot of particle counting box line in the fiber cross region of Example 1, Comparative Example 6 and Comparative Example 11.

[0062] Figure 13 The image shows a two-dimensional scatter plot of tensile index versus air permeability for Example 1, Comparative Example 7, and Comparative Example 8.

[0063] Figure 14 The image shows the scatter plot of the strength-permeability balance index for Examples 1, 7, and 8.

[0064] Figure 15 Two-dimensional scatter plots of quantification and compactness for Example 1, Comparative Example 7, and Comparative Example 8.

[0065] Figure 16 This is a macroscopic optical photograph of the high-strength breathable cup lid paper of Example 1.

[0066] Figure 17 This is a SEM image of the high-strength breathable cup lid paper from Example 1; Figure 17 a is a low-magnification SEM image of the high-strength breathable cup lid paper fiber network structure of Example 1; Figure 17 b and Figure 17 c is a medium-to-high magnification SEM image of the distribution of core-shell microparticles in the fiber overlap area of ​​the high-strength breathable cup lid paper in Example 1; Figure 17 d is a SEM image of the cross-section of the high-strength breathable cup lid paper in the thickness direction of Example 1.

[0067] Figure 18 This is a TEM characterization image of porous starch@citric acid crosslinked cationic starch core-shell microparticles and their fiber interface in the high-strength breathable cup lid paper of Example 1; Figure 18 a is a bright-field TEM cross-sectional image of the core-shell microparticles in Example 1; Figure 18 b is a magnified TEM image of the core-shell microparticle porous starch core and shell structure in Example 1; Figure 18 c is an HRTEM image of the interface between the core-shell microparticles and cellulose in Example 1. Detailed Implementation

[0068] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0069] Example 1 Overall production scale and product form This embodiment prepares a high-strength, breathable cup lid paper with a total oven-dry component weight of 1000g. The product form is a thick paper sheet without a continuous plastic coating layer. In the final oven-dry component, pulp fiber accounts for 980g, and porous starch@citric acid crosslinked cationic starch core-shell microparticles account for 20g. The pulp fiber consists of 343g of softwood pulp and 637g of hardwood pulp, with softwood pulp accounting for 35wt% of the oven-dry weight of the pulp fiber and hardwood pulp accounting for 65wt%.

[0070] Raw materials, components or material specifications This embodiment uses food-grade starch with a moisture content ≤13wt%, commercially available; medium-temperature α-amylase and amyloglucosidase are commercially available enzyme preparations for food processing, and the quality and specific activity of the enzyme preparations were recorded before use; anhydrous citric acid and sodium citrate dihydrate are analytical grade and commercially available; sodium chloride, sodium hydroxide, and hydrochloric acid are analytical grade and commercially available; 3-chloro-2-hydroxypropyltrimethylammonium chloride is a commercially available aqueous solution, and the effective content was recorded before calculating the feed amount; softwood pulp and hardwood pulp are food packaging pulps, commercially available.

[0071] Step 1: Preparation of porous starch cores 100 parts by weight of starch were added to 250 parts by weight of deionized water and mechanically stirred at 300 rpm for 20 min under air atmosphere and normal pressure to form a starch dispersion. A buffer system consisting of anhydrous citric acid and sodium citrate dihydrate was added to adjust the pH to 4.6. 0.05 parts by weight of mesophilic α-amylase and 0.02 parts by weight of amylase were added to the dispersion, and hydrolysis was carried out at 38 °C for 1 h. Stirring was maintained at 300 rpm during hydrolysis, and the endpoint was determined by a weight loss of 10 wt%. The system was then heated to 85 °C and held for 10 min to inactivate the enzymes. The resulting solid was washed with deionized water until the pH of the washings reached 5.5, and then dried with hot air at 45 °C for 4 h to obtain porous starch cores. The D50 of the obtained porous starch cores was 6.4 μm, the pore size was 0.30 μm, and the moisture content was 6 wt%.

[0072] Step 2: Preparation of cationic starch 100 parts by weight of starch, 120 parts by weight of deionized water, and 5 parts by weight of sodium chloride were mixed and stirred at 300 rpm for 30 min under air atmosphere and normal pressure to obtain a starch slurry. 2 parts by weight of sodium hydroxide were added to the starch slurry to adjust the pH to 10.5. Then, 10 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride were added, and the etherification reaction was carried out at 35℃ for 2 h with stirring at 300 rpm. After the reaction, the pH was adjusted to 6.0 with hydrochloric acid, the mixture was washed twice with deionized water, and dried at 40℃ for 6 h to obtain cationic starch. The degree of cationic substitution was 0.015 based on nitrogen content; the residual cationic etherifying agent content was 60 mg / kg; and the moisture content was 6 wt%.

[0073] Step 3: Preparation of porous starch@citric acid crosslinked cationic starch core-shell microparticles 100 parts by weight of porous starch cores were dispersed in deionized water and stirred at 300 rpm for 15 min. 8 parts by weight of cationic starch (dry basis) were added to adjust the solid content of the system to 10 wt%. 1 part by weight of anhydrous citric acid was added to adjust the pH to 3.5. The mixture was stirred at 45°C for 20 min under air atmosphere and normal pressure to allow the cationic starch to adsorb onto the surface of the porous starch cores. The gelatinization initiation temperature of the porous starch cores was determined to be 70°C by differential scanning calorimetry, and the adsorption temperature was lower than this gelatinization initiation temperature. The dispersion was dried in hot air at 50°C for 4 h to obtain pre-coated particles. The pre-coated particles were heat-cured at 115°C for 5 min to form a citric acid cross-linked cationic starch shell with the anhydrous citric acid. The heat-cured product was rinsed once with deionized water and dried at 45°C for 2 h to obtain porous starch@citric acid cross-linked cationic starch core-shell microparticles.

[0074] Step 4: Pulp system preparation, forming, pressing, drying and hot pressing finishing Softwood pulp and hardwood pulp were dispersed in deionized water to form a pulp fiber stock with a mass concentration of 0.3 wt% and a pH of 5.5. 20 g of porous starch@citric acid crosslinked cationic starch core-shell microparticles were pre-dispersed in deionized water and added to the pulp fiber stock 5 minutes before entering the forming wire, after stirring at 300 rpm for 10 minutes. Stirring was maintained at 250 rpm until no visible agglomerates were found in the pulp system. The pulp system was fed into the forming wire for forming, and the wet paper sheet was pressed at 80 kN / m linear pressure, then dried at 80℃ to a moisture content of 4 wt%. The dried paper sheet was then hot-pressed at 90℃, with a linear pressure of 30 kN / m for 0.2 s to obtain a high-strength, breathable cup lid paper.

[0075] Quality testing methods and results The porous starch-citric acid cross-linked cationic starch core-shell microparticles had a D50 of 8 μm as determined by laser diffraction particle size distribution; the shell thickness was 0.10 μm, with a coating efficiency of 75%, as determined by transmission electron microscopy cross-sectional images; the free citric acid content was 0.02 wt%, determined by high-performance liquid chromatography with external standard method; the dry basis weight ratio of the porous starch core to the citric acid cross-linked cationic starch shell was 100:8, calculated by material balance; the degree of cationic substitution of the shell was 0.010; and the zeta potential was +5 mV. The paper basis weight was 240 g / m³. 2 The air permeability was 1.20 μm / (Pa·s), the tensile index was 45 N·m / g, and the test results are expressed as mean ± standard deviation, n=3, with the standard deviation not exceeding 5% of the corresponding mean. The core-shell microparticle D500 before addition was 8.0 μm, and the core-shell microparticle D501 obtained by sampling the pulp fiber slurry before entering the forming wire was 7.92 μm, with a breakage rate of 1%. The retention rate was 70%. The paper thickness was 0.53 mm, and the density was 0.45 g / cm³. 3 The coefficient of variation in the thickness direction is 5%. Cross-sectional micrographs show that the core-shell microparticles can be located in the area where two pulp fibers are in contact or overlap, and can simultaneously contact the surfaces of the two pulp fibers.

[0076] Features and application scenarios of this embodiment This embodiment employs a relatively conservative low-ratio formulation, with a higher proportion of pulp fiber and a lower amount of core-shell microparticles. The conditions for enzymatic hydrolysis, etherification, adsorption, thermal curing, pressing, and hot-press finishing are all geared towards a milder range. The resulting paper maintains high air permeability and low density, making it suitable for producing cup lids for cold or room-temperature beverages where high moisture release and mild forming loads are required.

[0077] Example 2 Overall production scale and product form This embodiment prepares a high-strength, breathable cup lid paper with a total oven-dry component weight of 1000g. The product form is a thick paper sheet without a continuous plastic coating layer. In the final oven-dry component, pulp fiber accounts for 900g, and porous starch@citric acid crosslinked cationic starch core-shell microparticles account for 100g. The pulp fiber consists of 675g of softwood pulp and 225g of bamboo pulp, with softwood pulp accounting for 75wt% of the oven-dry weight of the pulp fiber and bamboo pulp accounting for 25wt%.

[0078] Raw materials, components or material specifications This embodiment uses food-grade starch with a moisture content ≤13wt%, commercially available; medium-temperature α-amylase and amyloglucosidase are commercially available enzyme preparations for food processing, and the quality and specific activity of the enzyme preparations were recorded before use; anhydrous citric acid and sodium citrate dihydrate are analytical grade and commercially available; sodium chloride, sodium hydroxide, and hydrochloric acid are analytical grade and commercially available; 3-chloro-2-hydroxypropyltrimethylammonium chloride is a commercially available aqueous solution, and the effective content was recorded before calculating the feed amount; softwood pulp and bamboo pulp are food packaging pulps and commercially available.

[0079] Step 1: Preparation of porous starch cores 100 parts by weight of starch were added to 600 parts by weight of deionized water and mechanically stirred at 500 rpm for 30 min under air atmosphere and normal pressure to form a starch dispersion. A buffer system consisting of anhydrous citric acid and sodium citrate dihydrate was added to adjust the pH to 6.2. 0.60 parts by weight of mesophilic α-amylase and 0.30 parts by weight of amylase were added to the dispersion, and hydrolysis was carried out at 58 °C for 4 h. During hydrolysis, stirring was maintained at 500 rpm, and the endpoint was determined by a weight loss of 35 wt%. The system was then heated to 100 °C and held for 30 min to inactivate the enzymes. The resulting solid was washed with deionized water until the pH of the washing solution reached 7.5, and then dried with hot air at 70 °C for 16 h to obtain porous starch cores. The D50 of the obtained porous starch cores was 23.4 μm, the pore size was 5.00 μm, and the moisture content was 13 wt%.

[0080] Step 2: Preparation of cationic starch 100 parts by weight of starch, 300 parts by weight of deionized water, and 20 parts by weight of sodium chloride were mixed and stirred at 500 rpm for 30 min under air atmosphere and normal pressure to obtain a starch slurry. 8 parts by weight of sodium hydroxide were added to the starch slurry to adjust the pH of the system to 12.0. Then, 35 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride were added, and the etherification reaction was carried out at 55℃ for 6 h with stirring at 500 rpm. After the reaction, the pH was adjusted to 7.5 with hydrochloric acid, the mixture was washed 5 times with deionized water, and dried at 65℃ for 18 h to obtain cationic starch. The degree of cationic substitution was 0.080 based on nitrogen content; the residual cationic etherifying agent content was 200 mg / kg; and the moisture content was 13 wt%.

[0081] Step 3: Preparation of porous starch@citric acid crosslinked cationic starch core-shell microparticles 100 parts by weight of porous starch cores were dispersed in deionized water and stirred at 500 rpm for 20 min. 35 parts by weight of cationic starch (dry basis) were added to adjust the solid content of the system to 35 wt%. 8 parts by weight of anhydrous citric acid were added to adjust the pH to 5.5. The mixture was stirred at 70°C for 90 min under air atmosphere and normal pressure to allow the cationic starch to adsorb onto the surface of the porous starch cores. The gelatinization initiation temperature of the porous starch cores was determined to be 75°C by differential scanning calorimetry, and the adsorption temperature was lower than this gelatinization initiation temperature. The dispersion was spray-dried at an inlet air temperature of 170°C and an outlet air temperature of 90°C to obtain pre-coated particles. The pre-coated particles were thermocured at 145°C for 30 min to form a citric acid crosslinked cationic starch shell with the anhydrous citric acid. The thermocure product was washed three times with deionized water and dried at 70°C for 8 h to obtain porous starch@citric acid crosslinked cationic starch core-shell microparticles.

[0082] Step 4: Pulp system preparation, forming, pressing, drying and hot pressing finishing Softwood pulp and bamboo pulp were dispersed in deionized water to form a pulp fiber stock with a mass concentration of 1.2 wt% and a pH of 7.5. 100 g of porous starch@citric acid crosslinked cationic starch core-shell microparticles were pre-dispersed in deionized water and added to the pulp fiber stock 30 minutes before entering the forming wire. After addition, stirring was maintained at 450 rpm until the core-shell microparticles were uniformly dispersed in the pulp system. The pulp system was fed into the forming wire for forming, and the wet paper sheet was pressed at 250 kN / m linear pressure, then dried at 120℃ to a moisture content of 10 wt%. The dried paper sheet was then hot-pressed at 135℃, with a linear pressure of 180 kN / m for 5.0 s to obtain a high-strength, breathable cup lid paper.

[0083] Quality testing methods and results The porous starch-citric acid cross-linked cationic starch core-shell microparticles had a D50 of 25 μm as determined by laser diffraction particle size distribution; the shell thickness was 0.80 μm as determined by transmission electron microscopy cross-sectional images, with a coating efficiency of 98%; the free citric acid content was 0.80 wt% as determined by high-performance liquid chromatography with external standard method; the dry basis weight ratio of the porous starch core to the citric acid cross-linked cationic starch shell was 100:35 according to material balance; the degree of cationic substitution of the shell was 0.070; and the zeta potential was +35 mV. The paper basis weight was 360 g / m³. 2The air permeability was 0.15 μm / (Pa·s), the tensile index was 85 N·m / g, and the test results are expressed as mean ± standard deviation, n=3, with the standard deviation not exceeding 5% of the corresponding mean. The core-shell microparticle D500 before addition was 25.0 μm, and the core-shell microparticle D501 obtained by sampling the pulp fiber slurry before entering the forming wire was 21.25 μm, with a breakage rate of 15%. The retention rate was 98%. The paper thickness was 0.40 mm, and the density was 0.90 g / cm³. 3 The coefficient of variation in the thickness direction was 25%. Cross-sectional micrographs showed that the core-shell microparticles were distributed between the fiber cross regions and adjacent pores, and the fiber network remained continuous.

[0084] Features and application scenarios of this embodiment This embodiment employs a high-load optimization scheme with a higher core-shell microparticle addition rate, and the shell construction, thermosetting, pressing, and hot-press finishing conditions are all in the high-value range. The resulting paper sheet has high basis weight, high density, and high tensile index, making it suitable for the production of hot beverage cup lids, takeaway shipping cup lids, and paper cup lids with high fastening strength requirements.

[0085] Example 3 Overall production scale and product form This embodiment prepares a high-strength, breathable cup lid paper with a total oven-dry component weight of 1000g. The product form is a thick paper sheet without a continuous plastic coating layer. In the final oven-dry component, pulp fiber accounts for 950g, and porous starch@citric acid crosslinked cationic starch core-shell microparticles account for 50g. The pulp fiber consists of 522.5g of softwood pulp, 237.5g of hardwood pulp, and 190g of bamboo pulp, with softwood pulp accounting for 55wt% of the oven-dry weight of the pulp fiber, hardwood pulp accounting for 25wt%, and bamboo pulp accounting for 20wt%.

[0086] Raw materials, components or material specifications This embodiment uses food-grade starch with a moisture content ≤13wt%, commercially available; medium-temperature α-amylase and amyloglucosidase are commercially available enzyme preparations for food processing, and the quality and specific activity of the enzyme preparations were recorded before use; anhydrous citric acid and sodium citrate dihydrate are analytical grade and commercially available; sodium chloride, sodium hydroxide, and hydrochloric acid are analytical grade and commercially available; 3-chloro-2-hydroxypropyltrimethylammonium chloride is a commercially available aqueous solution, and the effective content was recorded before calculating the feed amount; softwood pulp, hardwood pulp, and bamboo pulp are food packaging pulps, commercially available.

[0087] Step 1: Preparation of porous starch cores 100 parts by weight of starch were added to 420 parts by weight of deionized water and mechanically stirred at 400 rpm for 25 min under air atmosphere and normal pressure to form a starch dispersion. A buffer system consisting of anhydrous citric acid and sodium citrate dihydrate was added to adjust the pH to 5.4. 0.30 parts by weight of mesophilic α-amylase and 0.16 parts by weight of amylase were added to the dispersion, and hydrolysis was carried out at 48 °C for 2.5 h. Stirring was maintained at 400 rpm during hydrolysis, and the endpoint was determined by a weight loss of 22 wt%. The system was then heated to 92 °C and held for 20 min to inactivate the enzymes. The resulting solid was washed with deionized water until the pH of the washings reached 6.5, and then dried with hot air at 55 °C for 10 h to obtain porous starch cores. The D50 of the obtained porous starch cores was 15.2 μm, the pore size was 2.20 μm, and the moisture content was 9 wt%.

[0088] Step 2: Preparation of cationic starch 100 parts by weight of starch, 210 parts by weight of deionized water, and 12 parts by weight of sodium chloride were mixed and stirred at 400 rpm for 30 min under air atmosphere and normal pressure to obtain a starch slurry. 5 parts by weight of sodium hydroxide were added to the starch slurry to adjust the pH of the system to 11.2. Then, 22 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride were added, and the etherification reaction was carried out at 45℃ for 4 h with stirring at 400 rpm. After the reaction, the pH was adjusted to 6.8 with hydrochloric acid, the mixture was washed three times with deionized water, and dried at 55℃ for 12 h to obtain cationic starch. The degree of cationic substitution was 0.045 based on nitrogen content; the residual cationic etherifying agent content was 120 mg / kg; and the moisture content was 9 wt%.

[0089] Step 3: Preparation of porous starch@citric acid crosslinked cationic starch core-shell microparticles 100 parts by weight of porous starch cores were dispersed in deionized water and stirred at 400 rpm for 15 min. 20 parts by weight of cationic starch (dry basis) were added to adjust the solid content of the system to 22 wt%. 4 parts by weight of anhydrous citric acid were added to adjust the pH to 4.5. The mixture was stirred at 58°C for 55 min under air atmosphere and normal pressure to allow the cationic starch to adsorb onto the surface of the porous starch cores. The gelatinization initiation temperature of the porous starch cores was determined to be 73°C by differential scanning calorimetry, and the adsorption temperature was lower than this gelatinization initiation temperature. The dispersion was spray-dried at an inlet air temperature of 120°C and an outlet air temperature of 60°C to obtain pre-coated particles. The pre-coated particles were thermocured at 130°C for 18 min to allow the anhydrous citric acid to form a citric acid crosslinked cationic starch shell. The thermocure product was washed twice with deionized water and dried at 55°C for 5 h to obtain porous starch@citric acid crosslinked cationic starch core-shell microparticles.

[0090] Step 4: Pulp system preparation, forming, pressing, drying and hot pressing finishing Softwood pulp, hardwood pulp, and bamboo pulp were dispersed in deionized water to form a pulp fiber stock with a mass concentration of 0.8 wt% and a pH of 6.5. 50 g of porous starch@citric acid crosslinked cationic starch core-shell microparticles were pre-dispersed in deionized water and added to the pulp fiber stock 18 minutes before entering the forming wire. After addition, stirring was maintained at 350 rpm until the core-shell microparticles were uniformly dispersed in the pulp system. The pulp system was fed into the forming wire for forming, and the wet paper sheet was pressed at 150 kN / m linear pressure, then dried at 100℃ to a moisture content of 7 wt%. The dried paper sheet was then hot-pressed at 112℃, with a linear pressure of 100 kN / m for 2.5 s to obtain a high-strength, breathable cup lid paper.

[0091] Quality testing methods and results The porous starch-citric acid cross-linked cationic starch core-shell microparticles had a D50 of 16 μm as determined by laser diffraction particle size distribution; the shell thickness was 0.45 μm, with a coating efficiency of 88%, as determined by transmission electron microscopy cross-sectional images; the free citric acid content was 0.30 wt%, determined by high-performance liquid chromatography with external standard method; the dry basis weight ratio of the porous starch core to the citric acid cross-linked cationic starch shell was 100:20, calculated by material balance; the degree of cationic substitution of the shell was 0.040; and the zeta potential was +20 mV. The paper basis weight was 300 g / m³. 2 The air permeability was 0.62 μm / (Pa·s), and the tensile index was 68 N·m / g. The statistical results in Table 1 are expressed as mean ± standard deviation. The core-shell microparticle D500 before addition was 16.0 μm, and the core-shell microparticle D501 obtained by sampling the pulp fiber slurry before it entered the forming wire was 15.04 μm, with a breakage rate of 6%. The retention rate was 85%. The sheet thickness was 0.44 mm, and the density was 0.68 g / cm³. 3 The coefficient of variation in the thickness direction was 15%. Cross-sectional micrographs showed that the core-shell particles were distributed in the fiber cross-section area and the edges of the inter-fiber pores, and the difference in the number of particles in the upper, middle and lower layers of the paper was under control.

[0092] Features and application scenarios of this embodiment This embodiment employs a medium-ratio spray drying route, introducing a combination of hardwood pulp and bamboo pulp into the pulp fibers, with process conditions falling within the middle range. The resulting paper sheet balances forming uniformity, air permeability, and tensile strength, making it suitable for paper cup lid production that meets the requirements of stiffness, air permeability, and large-scale continuous forming.

[0093] Example 4 Overall production scale and product form This embodiment prepares a high-strength, breathable cup lid paper with a total oven-dry component weight of 1000g. The product form is a thick paper sheet without a continuous plastic coating layer. In the final oven-dry component, pulp fiber accounts for 920g, and porous starch@citric acid crosslinked cationic starch core-shell microparticles account for 80g. The pulp fiber consists of 414g of softwood pulp, 276g of hardwood pulp, and 230g of bagasse pulp, with softwood pulp accounting for 45wt% of the oven-dry weight of the pulp fiber, hardwood pulp accounting for 30wt%, and bagasse pulp accounting for 25wt%.

[0094] Raw materials, components or material specifications This embodiment uses food-grade starch with a moisture content ≤13wt%, commercially available; medium-temperature α-amylase and amyloglucosidase are commercially available enzyme preparations for food processing, and the quality and specific activity of the enzyme preparations were recorded before use; anhydrous citric acid and sodium citrate dihydrate are analytical grade and commercially available; sodium chloride, sodium hydroxide, and hydrochloric acid are analytical grade and commercially available; 3-chloro-2-hydroxypropyltrimethylammonium chloride is a commercially available aqueous solution, and the effective content was recorded before calculating the feed amount; softwood pulp, hardwood pulp, and bagasse pulp are food packaging pulps, commercially available.

[0095] Step 1: Preparation of porous starch cores 100 parts by weight of starch were added to 500 parts by weight of deionized water and mechanically stirred at 450 rpm for 30 min under air atmosphere and normal pressure to form a starch dispersion. A buffer system consisting of anhydrous citric acid and sodium citrate dihydrate was added to adjust the pH to 5.0. 0.45 parts by weight of mesophilic α-amylase and 0.22 parts by weight of amylase were added to the dispersion, and hydrolysis was carried out at 52 °C for 3 h. During hydrolysis, stirring was maintained at 450 rpm, and the endpoint was determined by a hydrolysis weight loss of 28 wt%. The system was then heated to 95 °C and held for 25 min to inactivate the enzymes. The resulting solid was washed with deionized water until the pH of the washing solution reached 7.0, and then dried with hot air at 60 °C for 14 h to obtain porous starch cores. The D50 of the obtained porous starch cores was 20.0 μm, the pore size was 3.80 μm, and the moisture content was 11 wt%.

[0096] Step 2: Preparation of cationic starch 100 parts by weight of starch, 260 parts by weight of deionized water, and 16 parts by weight of sodium chloride were mixed and stirred at 450 rpm for 30 min under air atmosphere and normal pressure to obtain a starch slurry. 6.5 parts by weight of sodium hydroxide were added to the starch slurry to adjust the pH of the system to 11.6. Then, 28 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride were added, and the etherification reaction was carried out at 50℃ for 5 h with stirring at 450 rpm. After the reaction, the pH was adjusted to 7.2 with hydrochloric acid, the mixture was washed four times with deionized water, and dried at 60℃ for 15 h to obtain cationic starch. The degree of cationic substitution was 0.060 based on nitrogen content; the residual cationic etherifying agent content was 80 mg / kg; and the moisture content was 11 wt%.

[0097] Step 3: Preparation of porous starch@citric acid crosslinked cationic starch core-shell microparticles 100 parts by weight of porous starch cores were dispersed in deionized water and stirred at 450 rpm for 15 min. 28 parts by weight of cationic starch (dry basis) were added to adjust the solid content of the system to 30 wt%. 6 parts by weight of anhydrous citric acid were added to adjust the pH to 4.0. The mixture was stirred at 62°C for 75 min under air atmosphere and normal pressure to allow the cationic starch to adsorb onto the surface of the porous starch cores. The gelatinization initiation temperature of the porous starch cores was determined to be 74°C by differential scanning calorimetry, and the adsorption temperature was lower than this gelatinization initiation temperature. The dispersion was dried in hot air at 80°C for 12 h to obtain pre-coated particles. The pre-coated particles were heat-cured at 140°C for 25 min to form a citric acid cross-linked cationic starch shell with the anhydrous citric acid. The heat-cured product was rinsed three times with deionized water and dried at 65°C for 7 h to obtain porous starch@citric acid cross-linked cationic starch core-shell microparticles.

[0098] Step 4: Pulp system preparation, forming, pressing, drying and hot pressing finishing Softwood pulp, hardwood pulp, and bagasse pulp were dispersed in deionized water to form a pulp fiber stock with a mass concentration of 1.0 wt% and a pH of 6.8. 80 g of porous starch@citric acid crosslinked cationic starch core-shell microparticles were pre-dispersed in deionized water and added to the pulp fiber stock 25 min before entering the forming wire. After addition, stirring was maintained at 400 rpm until the core-shell microparticles were uniformly dispersed in the pulp system. The pulp system was fed into the forming wire for forming, and the wet paper sheet was pressed at 220 kN / m linear pressure, then dried at 110℃ to a moisture content of 8 wt%. The dried paper sheet was then hot-pressed at 125℃, with a linear pressure of 150 kN / m for 4.0 s to obtain a high-strength, breathable cup lid paper.

[0099] Quality testing methods and results The porous starch-citric acid cross-linked cationic starch core-shell microparticles had a D50 of 22 μm as determined by laser diffraction particle size distribution; the shell thickness was 0.65 μm, with a coverage rate of 94%, as determined by transmission electron microscopy cross-sectional images; the free citric acid content was 0.55 wt%, determined by high-performance liquid chromatography with external standard method; the dry basis weight ratio of the porous starch core to the citric acid cross-linked cationic starch shell was 100:28, calculated by material balance; the degree of cationic substitution of the shell was 0.058; and the zeta potential was +28 mV. The paper basis weight was 330 g / m³. 2The air permeability was 0.38 μm / (Pa·s), the tensile index was 78 N·m / g, and the test results are expressed as mean ± standard deviation, n=3, with the standard deviation not exceeding 5% of the corresponding mean. The core-shell microparticle D500 before addition was 22.0 μm, and the core-shell microparticle D501 obtained by sampling the pulp fiber slurry before entering the forming wire was 19.80 μm, with a breakage rate of 10%. The retention rate was 93%. The paper thickness was 0.40 mm, and the density was 0.82 g / cm³. 3 The coefficient of variation in the thickness direction is 8%. Cross-sectional micrographs show that core-shell microparticles form numerous contact points in the fiber cross-section area, and the paper pores maintain a continuous distribution.

[0100] Features and application scenarios of this embodiment This embodiment employs a high-load compounding scheme with bagasse pulp, and utilizes hot-air drying under high-strength conditions and strong hot-press finishing conditions. The resulting paper maintains usable air permeability even with high basis weight and high density, making it suitable for cup lid paper production that requires a balance between diverse plant fiber sources, high stiffness, and stability in food packaging processing.

[0101] Comparative Example 1: It is basically the same as Example 1, except that in step 4, the porous starch@citric acid crosslinked cationic starch core-shell microparticles in the final oven-dried component are 10g, the pulp fiber is 990g, and the softwood pulp and hardwood pulp are still prepared according to 35wt% and 65wt% of the oven-dried mass of the pulp fiber, respectively, with other conditions remaining unchanged.

[0102] Comparative Example 2: Basically the same as Example 1, except that in step 1, medium-temperature α-amylase and amyloglucosidase were not added, and no enzymatic hydrolysis was performed. Food-grade starch was stirred at 38°C for 1 hour in a buffer system with pH 4.6, then heated to 85°C and held for 10 minutes. The starch was then washed until the pH of the washing solution was 5.5 and dried with hot air at 45°C for 4 hours to obtain untreated starch nuclei. Other conditions remained unchanged.

[0103] Comparative Example 3: It is basically the same as Example 1, except that in step 3, the dry basis feeding ratio of porous starch core to cationic starch is adjusted to 100:4, that is, 100 parts by weight of porous starch core is dispersed in deionized water and then 4 parts by weight of cationic starch is added on a dry basis, and other conditions remain unchanged.

[0104] Comparative Example 4: It is basically the same as Example 1, except that the amount of anhydrous citric acid added in step 3 is 9 parts by weight. After adding it, the pH is still adjusted to 3.5, and after stirring at 45°C for 20 min, it is dried with hot air at 50°C for 4 h and heat-cured at 115°C for 5 min. Other conditions remain unchanged.

[0105] Comparative Example 5: It is basically the same as Example 1, except that the thermosetting temperature of the pre-coated particles in step 3 is 100°C, the thermosetting time is still 5 min, and other conditions remain unchanged.

[0106] Comparative Example 6: It is basically the same as Example 1, except that the porous starch@citric acid crosslinked cationic starch core-shell microparticles are added 2 minutes before entering the forming mesh in step 4. After addition, the stirring is maintained at 250 rpm until entering the forming mesh, and other conditions remain unchanged.

[0107] Comparative Example 7: Basically the same as Example 1, except that the linear pressure of the wet paper sheet in step 4 is 50 kN / m, and other conditions remain unchanged.

[0108] Comparative Example 8: It is basically the same as Example 1, except that the hot pressing finishing temperature in step 4 is 70°C, the linear pressure is still 30kN / m, the time is still 0.2s, and other conditions remain unchanged.

[0109] Comparative Example 9: Essentially the same as Example 1, except that the porous starch core was removed. Cationic starch, anhydrous citric acid, and deionized water were dispersed according to the amounts of cationic starch and anhydrous citric acid used in step 3 of Example 1, followed by pH adjustment, drying, and heat curing at 115°C for 5 minutes to obtain citric acid-crosslinked cationic starch microparticles. 20g of these microparticles were added to the pulp fiber slurry, with other conditions remaining unchanged. This comparative example was used to verify the synergistic effect of the porous starch core and the citric acid-crosslinked cationic starch shell.

[0110] Comparative Example 10: Essentially the same as Example 1, except that only the porous starch core was retained without the addition of cationic starch and anhydrous citric acid. In step 3, the porous starch core obtained in step 1 was pre-dispersed in deionized water at a rate of 20g and then added to the pulp fiber slurry. Other conditions remained unchanged. This comparative example was used to verify the synergistic effect of the porous starch core and the citric acid-crosslinked cationic starch shell.

[0111] Comparative Example 11: Essentially the same as Example 1, except that the key interface construction sequence in step 3—"cationic starch first adsorbs onto the surface of porous starch cores, then dries to form pre-coated particles, and then heat-cures"—was omitted. Instead, 8 parts by weight of cationic starch and 1 part by weight of anhydrous citric acid were mixed in an aqueous medium at pH 3.5 and heat-cured at 115°C for 5 minutes. After drying, cross-linked cationic starch powder was obtained, which was then dry-mixed with 100 parts by weight of porous starch cores for 10 minutes and added to pulp fiber slurry as a substitute for non-in-situ coated core-shell microparticles. Other conditions remained unchanged. This comparative example was used to verify the synergistic effect of the interface construction sequence between porous starch cores and citric acid-crosslinked cationic starch shells.

[0112] Characterization and performance testing: Standard Verification Instructions: In experimental testing, the air permeability, tensile strength, standard atmospheric conditioning, basis weight, thickness, and moisture content of paper and paperboard shall preferentially adopt the relevant current standards displayed in the national standard full-text publication system. Specifically, GB / T 458-2008 is the current standard for determining the air permeability of paper and paperboard; GB / T 12914-2018 is the current standard for the constant-rate tensile strength test of paper and paperboard; and GB / T 10739-2023 is the current standard for standard atmospheric conditions for the treatment and testing of paper, paperboard, and pulp samples. Basis weight testing can refer to GB / T 451.2-2023, and thickness testing can refer to GB / T 451.3-2002. Moisture content determination shall preferentially adopt the current GB / T 462-2023; the original GB / T 462-2008 is now obsolete.

[0113] Air permeability testing is used to evaluate the gas channel retention ability of high-strength, breathable cup lid paper under conditions without a continuous plastic coating layer. Paper sheets, after atmospheric equilibrium according to GB / T 10739-2023 standard, are cut into samples with suitable clamping areas. Air permeability testing is performed using an air permeability tester according to GB / T 458-2008. The unit pressure difference and the air flow rate through a unit area of ​​paper per unit time are recorded, and the results are expressed in μm / (Pa·s). Each group contains at least 5 sheets, and samples with obvious clamping leakage are discarded. The mean, standard deviation, and coefficient of variation are calculated to compare the effects of forming, pressing, hot pressing, and core-shell microparticle structure on the air permeability channels.

[0114] The tensile index test is used to evaluate the fiber bond strength and load-bearing capacity of high-strength, breathable cup lid paper. After conditioning the paper sheet according to GB / T 10739-2023, test strips are cut along the longitudinal and transverse directions. Tensile strength is measured using a constant-speed tensile testing machine at a tensile speed of 20 mm / min according to GB / T 12914-2018. The tensile index is calculated based on the basis weight, with units of N·m / g. At least five strips are tested in each direction. Abnormal breakage samples are recorded and discarded according to standards. The mean ± standard deviation is output to determine the reinforcing effect of core-shell microparticles in the fiber cross-linking region.

[0115] Basis weight, thickness, and density tests are used to evaluate the uniformity of cup lid paper formation and the sheet structure after pressing and hot pressing finishing. After standard atmospheric equilibration, the basis weight is determined according to GB / T 451.2-2023, and the sheet thickness is determined according to GB / T 451.3-2002. Density is then calculated from basis weight and thickness. At least 10 locations are taken for each group, avoiding edges and obvious defect areas. The basis weight (g / m³) is output. 2 Thickness (mm) and density (g / cm) 3 The mean and standard deviation are used to correlate air permeability, tensile index and paper density.

[0116] The particle size and breakage rate of core-shell microparticles were tested to evaluate the structural retention of porous starch@citric acid crosslinked cationic starch core-shell microparticles after they entered the pulp system. Before addition, the D500 of the aqueous dispersion of the core-shell microparticles was measured. After entering the pulp fiber slurry and before entering the forming wire, samples were taken, and after gentle sieving to remove long fibers, the D501 was measured. D10, D50, and D90 were recorded using laser diffraction particle size distribution. The breakage rate was calculated as (D500-D501) / D500×100%, with each group tested in triplicate. This was used to evaluate the effects of stirring, addition timing, and shell thermal curing conditions on microparticle integrity.

[0117] The core-shell microparticle retention test is used to evaluate the retention stability between the positively charged cross-linked shell layer and the pulp fiber network. The nitrogen content of the pulp fibers before the addition of core-shell microparticles, the nitrogen content of the core-shell microparticles, and the nitrogen content of the paper sheet after papermaking were measured. After subtracting the background nitrogen from the pulp fibers, the dry basis mass of the core-shell microparticles in the paper sheet was calculated. The retention rate was calculated as (dry basis mass of core-shell microparticles in the paper sheet / dry basis mass of core-shell microparticles added to the pulp fiber pulp) × 100%, with three parallel tests performed. The mean, standard deviation, and recovery rate were output for verification.

[0118] The free citric acid content assay was used to evaluate the residual levels of migratable small molecules in the citric acid-crosslinked cationic starch shell. Washed and dried core-shell microparticles were extracted with deionized water at a fixed solid-liquid ratio. After centrifugation or filtration, the citric acid peak area was determined using high-performance liquid chromatography (HPLC) with external standard method, and the free citric acid mass was calculated according to the standard curve. Results are expressed as free citric acid mass / core-shell microparticle mass × 100%, and were performed in triplicate. The limit of detection, linear range, and spiked recovery rate were recorded to support the evaluation of low migration.

[0119] The strength-breathability balance index is used to comprehensively evaluate the degree of synergy between mechanical strength and breathability. It uses the breathability P measured by the breathability test and the tensile index T measured by the tensile index test as inputs, and calculates the index using the formula: I = 100 / [1 + ((85-T) / 40)]. 2 +((P-0.60) / 0.60) 2 The equilibrium index is calculated only as a comparison indicator between samples and does not replace the standard tests for air permeability and tensile index. For each sample, the average values ​​of P and T in the same batch are taken, and the standard deviation is estimated using the error propagation method. A two-dimensional scatter plot of T-P and a bar chart of I value are then plotted.

[0120] Figure 1 The images show the TEM shell thickness probability density distribution of Example 1, Comparative Example 10, and Comparative Example 11. Figure 2 Box plots of TEM shell thickness for Examples 1, 10, and 11. Figure 1It is evident that the shell thickness in Example 1 is mainly concentrated in the range of approximately 0.08–0.12 μm, with a concentrated peak in the probability density curve and a narrow distribution range; Comparative Example 10 basically did not form an effective shell, and although Comparative Example 11 had a certain encapsulation structure, the shell thickness was thin and the distribution was discrete. Further combining... Figure 2 As can be seen, the median shell thickness in Example 1 is approximately 0.10 μm, with minimal inter-particle variation, while the shell thickness in Comparative Example 10 is close to zero, and the distribution range of the boxes and scattered particles in Comparative Example 11 is wider. These results demonstrate that the interface construction method of first adsorption coating followed by thermal curing can form a cationic starch shell of moderate thickness and good continuity on the surface of porous starch cores, thus providing a stable microstructural basis for subsequent particle retention, fiber bridging, and paper reinforcement.

[0121] Figure 3 This is a cumulative distribution chart of TEM coverage for Example 1, Comparative Example 10, and Comparative Example 11. Figure 4 Box plots of TEM coverage for Examples 1, 10, and 11. Figure 3 As can be seen, the particle coating rate of Example 1 is mainly distributed in the range of 70%–85%, and the cumulative distribution curve shifts towards the high coating rate region, indicating that most particles have a high degree of outer layer coverage; the coating rate of Comparative Example 10 is generally at a lower level, and the coating rate of Comparative Example 11 is significantly lower than that of Example 1. Figure 4 Furthermore, it can be seen that the median coating rate of Example 1 is approximately 75%, and the scatter points are concentrated, indicating that the coating integrity among different particles has good consistency; while Comparative Example 10 only shows a small amount of discontinuous adhesion, and Comparative Example 11 has problems with insufficient coating and increased dispersion. Combined with... Figure 1 and Figure 2 The results of the shell thickness show that Example 1 can not only form a suitable shell thickness of about 0.10 μm, but also maintain a high coverage rate of about 75%, indicating that its core-shell structure construction process has good controllability and repeatability.

[0122] Figure 5 The above are the superimposed FTIR absorbance spectra of Example 1, Comparative Example 5, and Comparative Example 11. Figure 6 The HPLC chromatograms of free citric acid for Examples 1, 5, and 11 are shown below. Figure 7 This is a scatter plot showing the average free citric acid content of Examples 1, 5, and 11. Figure 5 As can be seen, Example 1 is at approximately 1730 cm -1 The absorption peaks related to ester groups in the vicinity are enhanced, especially in the range of 1020–1155 cm⁻¹. -1The region still retains the characteristic peaks of the starch skeleton, indicating that citric acid participated in the cross-linking reaction of the cationic starch shell without destroying the main starch structure. In contrast, the peak intensities in the corresponding regions of Comparative Examples 5 and 11 are weaker, indicating that the degree of cross-linking is limited when the thermosetting conditions or interface construction sequence are insufficient. Figure 6 It can be seen that the chromatographic response peak area near the citric acid retention time in Example 1 is smaller, while the peak areas in Comparative Examples 5 and 11 are larger; further from Figure 7 Quantitative results show that the free citric acid content in Example 1 is approximately 0.02 wt%, lower than approximately 0.05 wt% in Comparative Example 5 and approximately 0.03 wt% in Comparative Example 11. The above FTIR and HPLC results corroborate each other, indicating that Example 1 can promote the effective participation of citric acid in shell crosslinking and reduce the residue of free citric acid, so that the core-shell microparticles have both structural stability and low residue levels.

[0123] Figure 8 This is a scatter plot of the mean retention rate of core-shell particles in Example 1, Comparative Example 6, and Comparative Example 10. Figure 9 This is a scatter plot showing the average nitrogen content after background subtraction for Examples 1, 6, and 10. During paper forming, the effective retention of microparticles is a prerequisite for them to exert their reinforcing and structural control functions. Figure 8 As can be seen, the core-shell particle retention rate of Example 1 is approximately 70%, significantly higher than that of Comparative Example 6 (approximately 49%) and Comparative Example 10 (approximately 35%). This result indicates that the cationic shell can enhance the interaction between the particles and the negatively charged pulp fibers, and that appropriate addition timing is beneficial for the capture and fixation of particles within the fiber network. Figure 9 It is evident that the background nitrogen content in the paper of Example 1 is higher than that of Comparative Example 6 and Comparative Example 10. Since nitrogen mainly originates from the nitrogen-containing cation shell, this result further illustrates that more cation core-shell particles are retained in the paper system. Figure 8 The quality remains the result and Figure 9 The elemental tracing results showed a consistent trend, jointly demonstrating that Example 1 has a significant advantage in particle retention.

[0124] Figure 10 The following are three-layer distribution diagrams in the thickness direction of the paper in Example 1, Comparative Example 6, and Comparative Example 11. Figure 11 This is a scatter plot showing the mean of the coefficient of variation in the thickness direction for Examples 1, 6, and 11. Figure 12 The image shows a scatter plot of particle counts in the fiber cross-section region for Examples 1, 6, and 11. Based on a high retention rate, the uniformity of particle distribution within the paper sheet further determines whether its reinforcing effect can be fully realized. Figure 10As can be seen, in Example 1, the distribution ratio of core-shell particles in the upper, middle, and lower layers is nearly uniform, all around 33%, with no obvious unilateral enrichment; while Comparative Examples 6 and 11 show more obvious interlayer shifts. Figure 11 As can be seen, the coefficient of variation in the thickness direction of Example 1 is only about 5%–10%, significantly lower than that of Comparative Example 6 and Comparative Example 11, indicating that it has better distribution uniformity in the thickness direction. Further... Figure 12 As can be seen, the particle count in the fiber crossover region of Example 1 is approximately 30 particles per field of view, which is higher than that of Comparative Example 6 and Comparative Example 11. This indicates that the core-shell microparticles can not only uniformly enter the thickness direction of the paper sheet, but also more easily locate in the fiber overlap and crossover regions. Since the fiber crossover region is a key area for stress transmission and bonding strength formation in the paper sheet, this distribution characteristic is beneficial for enhancing the interfacial bonding between fibers and provides a structural basis for improving paper sheet strength.

[0125] Figure 13 The above are two-dimensional scatter plots of tensile index versus air permeability for Examples 1, 7, and 8. Figure 14 This is a scatter plot of the strength-permeability balance index for Example 1, Comparative Example 7, and Comparative Example 8. Figure 15 Two-dimensional scatter plots of quantitation and compactness for Examples 1, 7, and 8. Figure 13 As can be seen, Example 1 has a tensile index of approximately 45 N·m / g, while maintaining an air permeability of approximately 1.20 μm / (Pa·s), indicating that it improves the mechanical strength of the paper while still retaining certain gas transport channels; Comparative Examples 7 and 8, on the other hand, exhibit insufficient strength or poor balance between strength and air permeability. Figure 14 Furthermore, it is evident that the strength-permeability balance index of Example 1 is higher than that of Comparative Examples 7 and 8, indicating that under the combined conditions of forming, pressing, drying, and hot-pressing finishing, the core-shell microparticles can effectively improve the overall performance of the paper sheet. Figure 15 It can be seen that the quantitative values ​​of the three groups of samples remained basically at approximately 240 g / m³. 2 Nearby, the density of Example 1 is approximately 0.45 g / cm. 3 The paper did not exhibit characteristics of strength improvement achieved through significantly increasing basis weight or excessive densification. This indicates that the performance improvement in Example 1 mainly stems from the enhancement of the fiber overlap interface by core-shell microparticles and the rational control of the paper pore structure, rather than simply relying on an increase in paper basis weight.

[0126] Figure 16 This is a macroscopic optical photograph of the high-strength, breathable cup lid paper from Example 1. Figure 16 As can be seen, the obtained sample is a white to light off-white matte opaque thick paper sheet without a continuous plastic coating layer, and the basis weight is 240 g / m³. 2The sample had a thickness of 0.53 mm and a moisture content of 4 wt%. The sample surface was continuous and intact, with no obvious macroscopic cracks, warping, or particle agglomeration observed, indicating that the forming, pressing, drying, and hot-pressing finishing processes could produce a thick paper sheet with a uniform appearance and stable structure. This macroscopic morphology result corresponds to the aforementioned high particle retention, uniform distribution in the thickness direction, and strength-air permeability balance results, indicating that Example 1 possesses the technological basis for achieving stable paper production and subsequent application performance.

[0127] Figure 17 This is a SEM image of the high-strength, breathable cup lid paper from Example 1. Figure 17 As seen in the low-magnification image, softwood pulp and hardwood pulp together form a continuous porous fiber network. No continuous plastic coating layer is observed on the paper surface, indicating that the paper's air permeability primarily originates from the interconnected pores retained within the fiber network. Figure 17 b and Figure 17 As seen in the high-magnification image (c), porous starch@citric acid crosslinked cationic starch core-shell microparticles are distributed in the overlapping region of pulp fibers. The D50 of the core-shell microparticles is 8 μm, and they form contact, filling, and bridging structures with adjacent fibers. Figure 17 As shown in the d-section image, the paper thickness is approximately 0.53 mm, with pores remaining between fiber layers, and the core-shell microparticles exhibiting a relatively uniform distribution along the thickness direction. This SEM result further illustrates that Example 1 did not improve strength by forming a continuous closed layer, but rather enhanced inter-fiber bonding through the bridging and reinforcing effects of the core-shell microparticles in the fiber overlap areas, while simultaneously preserving necessary pores, thereby supporting an air permeability of approximately 1.20 μm / (Pa·s) and relatively high paper strength.

[0128] Figure 18 This is a TEM image showing the porous starch@citric acid crosslinked cationic starch core-shell microparticles and their fiber interface in the high-strength breathable cup lid paper of Example 1. Figure 18 As seen in the bright-field TEM cross-sectional image, the core-shell microparticles consist of a porous starch core and a citric acid-crosslinked cationic starch shell, with a particle D50 of 8 μm. Figure 18 As shown in the magnified image (b), the porous starch core has a pore size of approximately 0.30 μm, a shell thickness of approximately 0.10 μm, and a coverage rate of approximately 75%. Figures 1 to 4 The results for shell thickness and coverage are consistent; from Figure 18 cHRTEM images show that the cellulose and starch-based organic phases exhibit a microstructure with both locally ordered and amorphous regions, indicating that the core-shell microparticles form a stable cross-linked shell while maintaining a porous core structure. Combined with the aforementioned retention, distribution, and performance results, it can be concluded that these core-shell microparticles can serve as microscale reinforcing units in the fiber overlap region, improving the inter-fiber bonding strength without blocking all pores. This explains, from a microstructural perspective, why the tensile index of approximately 45 N·m / g and the air permeability of approximately 1.20 μm / (Pa·s) in Example 1 can be synergistically achieved.

[0129] Table 1 Performance of Examples and Comparative Examples ; As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1 to 4 form a relatively complete performance gradient among air permeability, tensile index, core-shell microparticle retention rate, breakage rate, free citric acid content, and thickness direction distribution variation coefficient. Among them, Examples 3 and 4 show a higher strength-air permeability balance index, indicating that medium-high load of core-shell microparticles, moderate shell thickness, sufficient thermosetting, and reasonable pressing and hot pressing finishing are beneficial to balancing fiber bonding and porosity retention. Comparative Example 1 showed a decrease in tensile index and retention rate after reducing the amount of core-shell microparticles. Comparative Examples 2 to 5, after changing the porous core formation method, shell ratio, citric acid dosage, and thermosetting temperature, exhibited one or more problems, including insufficient porous structure, insufficient shell coverage, deviation of crosslinking / residual control, or insufficient interface fixation, leading to a decrease in fiber network bonding ability. Comparative Example 6 showed an increase in the distribution variation coefficient after changing the addition time. Comparative Examples 7 and 8 showed a decrease in tensile index after weakening pressing or hot pressing finishing. Comparative Examples 9 to 11 showed a decrease in retention rate, tensile index, and comprehensive balance index after dismantling or destroying the synergistic interface between the porous core and the crosslinked cationic shell, demonstrating that the synergistic design of the core-shell interface plays a key role in solving the problem of balancing strength and air permeability.

[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A preparation process for a high-strength, breathable cup lid paper, characterized in that, Includes the following steps: S1. Provides pulp fiber pulp and porous starch-citric acid crosslinked cationic starch core-shell microparticles; S2. The porous starch-citric acid cross-linked cationic starch core-shell microparticles are added to the pulp fiber pulp to form a pulp system containing porous starch-citric acid cross-linked cationic starch core-shell microparticles; S3. The pulp system containing porous starch-citric acid crosslinked cationic starch core-shell microparticles is formed, pressed, dried and hot-pressed to obtain high-strength breathable cup lid paper; The high-strength breathable cup lid paper does not have a continuous plastic coating layer. Based on 100 parts by weight of the total amount of the oven-dry final components in the high-strength breathable cup lid paper, the high-strength breathable cup lid paper comprises: 90.0–98.0 parts by weight of pulp fiber, wherein the pulp fiber comprises one or more of softwood pulp, hardwood pulp, bamboo pulp and bagasse pulp; Porous starch-citric acid crosslinked cationic starch core-shell microparticles 2.0–10.0 parts by weight; The sum of the weight parts of the pulp fiber and the porous starch-citric acid crosslinked cationic starch core-shell microparticles is 100 parts by weight. The porous starch-citric acid crosslinked cationic starch core-shell microparticles are prepared by the following steps: A1. Provides porous starch cores and cationic starch; A2. Disperse the porous starch core in an aqueous medium, add the cationic starch, and adjust the solid content of the system; A3. Add citric acid crosslinking agent and adjust pH, and under heating and stirring conditions, allow the cationic starch to adsorb onto the surface of the porous starch core to obtain a dispersion; A4. The dispersion is dried to obtain pre-coated particles; A5. The pre-coated particles are heat-cured at 115–145°C for 5–30 min to allow the citric acid crosslinking agent to form an ester crosslink with the cationic starch, thereby obtaining a heat-cured product; The pulp fibers include softwood pulp, as well as one or more of hardwood pulp, bamboo pulp, or bagasse pulp; the basis weight of the high-strength, breathable cup lid paper is 240–360 g / m³. 2 The air permeability is 0.15–1.20 μm / (Pa·s), and the tensile index is 45–85 N·m / g; In step S2, the pulp fiber slurry has a mass concentration of 0.3–1.2 wt% and a pH of 5.5–7.5, and the porous starch-citric acid crosslinked cationic starch core-shell microparticles are added 5–30 min before entering the forming wire. In step S3, the formed wet paper sheet is pressed and dried. The pressing linear pressure is 80–250 kN / m, the drying temperature is 80–120°C, and the wet paper sheet is dried to a moisture content of 4–10 wt%. In step S3, the hot pressing finishing temperature is 90–135℃, the linear voltage is 30–180kN / m, and the time is 0.2–5.0s.

2. The preparation process of the high-strength breathable cup lid paper according to claim 1, characterized in that, The porous starch-citric acid crosslinked cationic starch core-shell microparticles include a porous starch core and a citric acid crosslinked cationic starch shell layer that at least partially covers the surface of the porous starch core; The porous starch-citric acid crosslinked cationic starch core-shell microparticles have a D50 of 8–25 μm, a shell thickness of 0.10–0.80 μm, and a coating rate of 75–98%.

3. The preparation process of the high-strength breathable cup lid paper according to claim 1, characterized in that, The thermosetting product is washed and dried to obtain the porous starch-citric acid crosslinked cationic starch core-shell microparticles; the free citric acid content of the porous starch-citric acid crosslinked cationic starch core-shell microparticles is 0.02–0.80 wt%, based on the mass of the porous starch-citric acid crosslinked cationic starch core-shell microparticles.

4. The preparation process of the high-strength breathable cup lid paper according to claim 1, characterized in that, The porous starch core is prepared by the following steps: B1. Disperse starch in an aqueous medium, add a buffer system, and adjust the pH to 4.6–6.2; B2. Add medium-temperature α-amylase and amylase to the dispersion obtained in step B1, and hydrolyze for 1–4 h under heating conditions of 38–58 °C. B3. When the starch hydrolysis weight loss reaches 10–35 wt%, heat the system to 85–100℃ and hold for 10–30 min to inactivate the enzyme; B4. Wash the solid obtained in step B3 until the pH of the washing solution is 5.5–7.5, and dry it at 45–70°C for 4–16 h to obtain the porous starch core; The porous starch core has a D50 of 6.4–23.4 μm, a pore size of 0.30–5.00 μm, and a moisture content of 6–13 wt%.

5. The preparation process of the high-strength breathable cup lid paper according to claim 1, characterized in that, The cationic starch is prepared by the following steps: C1. Mix starch, aqueous medium and inorganic salt to obtain starch slurry; C2. Add an alkaline regulator to the starch slurry to adjust the pH to 10.5–12.0; C3. Add a cationic etherifying agent to the system obtained in step C2 and etherify it under heating conditions of 35–55°C for 2–6 hours; C4. Adjust the pH to 6.0–7.5, then wash 2–5 times and dry at 40–65°C for 6–18 h to obtain the cationic starch; The cationic starch has a degree of cationic substitution of 0.015–0.080, a residual cationic etherifying agent content of no more than 200 mg / kg based on the mass of the cationic starch, and a moisture content of 6–13 wt%.

6. The preparation process of the high-strength breathable cup lid paper according to claim 1, characterized in that, In the porous starch-citric acid crosslinked cationic starch core-shell microparticles, the dry weight ratio of the porous starch core to the citric acid crosslinked cationic starch shell is 100:8–35, the degree of cationic substitution of the citric acid crosslinked cationic starch shell is 0.010–0.070, and the retention rate of the porous starch-citric acid crosslinked cationic starch core-shell microparticles in the high-strength breathable cup lid paper is 70–98%.

Citation Information

Patent Citations

  • A kind of paper cup cover and its processing technology

    CN106335702B

  • Environmental protection paper cup lid

    CN204979661U

  • Production process for filled paper and filled paper

    CN103352395A

  • Preparation method of low-basis-weight high-air-permeability packaging base paper

    CN111608018A